(untitled) (Bangladesh Journal of Animal Science, 2013)
Twelve indigenous growing cattle (live weight 130.00 ± 1.67 kg) were selected and divided into four groups having three animals in each group. Group A, B, C and D supplied 3.0% urea + 2.0% midden soil, 3.0% urea + 3.0% midden soil, 3.0% urea + 4.0% midden soil and 3.0% urea + 5.0% midden soil treated rice straw. In addition to this all the animals were supplied 2 Kg green grass, 450 g concentrate mixture and 40 g salt per 100 kg body weight. Rice straw treated with 3.0% urea+ 2.0% midden soil resulted an improvement in crude protein content of rice straw from 3.30 to 7.08% which was further increased by 7.40, 7.90 and 8.14% treatment with 3.0% urea + 3.0% midden soil, 3.0% urea + 4.0% midden soil and 3.0% urea + 5.0% midden soil respectively. The addition of 5.0% midden soil as a urease source with 3.0% urea (D) treated rice straw not only significantly (P<0.01) increased the coefficient of digestibility of DM, CP, CF, EE and NFE but also significantly (P<0.05) increased the coefficient of digestibility of OM than other treatments. Digestible organic matter (DOM), crude protein (DCP), digestible crude fibre (DCF), digestible nitrogen free extract (DNFE) and total digestible nutrients (TDN) contents were significantly (p<0.01) higher in diet D in comparison to diet A, B and C. DOI: http://dx.doi.org/10.3329/bjas.v42i1.15770 Bang. J. Anim. Sci. 2013. 42 (1): 29-34